Effects of a broad range of experimental temperatures on the population growth and body-size of five species of free-living nematodes. (February 2019) - Majdi, Nabil; Traunspurger, Walter; Fueser, Hendrik; Gansfort, Birgit; Laffaille, Pascal; Maire, Anthony
Abstract: The temperature-size rule postulates that the growth rates of ectotherms increase under rising temperatures, while the sizes of these organisms at maturity decrease. However, the upper temperature-tolerance range is also typically represented by a metabolic tipping point after which growth suddenly ceases. Free-living nematodes are important members of ecosystems, but little is known about their thermal tolerance. In the present study we measured the population growth rates and body-size distributions of five species of free-living bacterivorous nematodes exposed in the laboratory to a broad range of temperatures. This allowed a determination of their different thermal tolerance ranges, even of closely related species, including Plectus acuminatus (thermal optimum of 20–25 °C) and P. cf. velox (10–15 °C). With the exception of Acrobeloides nanus, which had the broadest thermal tolerance range, the population growth of the other species declined between 25 and 30 °C. Our results were consistent with the temperature-size rule, as the body-size of the tested species at maturity decreased with increasing temperature. This reduction was accompanied by a smaller number of eggs carried by mature females. Although our study was purely experimental, it suggests that heat waves or other alterations in the thermal regime affect the population dynamics and body-size structure of nematode communities in the field. Highlights: Close nematode species can show contrasted growth patterns in response to temperature gradient. Body-size at maturity declines with increasing temperature. The number of eggs carried in the uterus declines with increasing temperature. Prevalence of early juvenile stages reduces body-mass structure with increasing temperature.